Implementing lean construction theory to construction processes waste management - Nikakhtar, Amin (2011)
Waste in the construction industry has been the subject of several research projects around the world in recent years. Researchers implement different methods to reduce the amount of waste in construction industry. One of effective methods is application of lean approach to construction industry. Lean construction is a result of the introduction of a new form of production management. Although lean construction is still evolving, the generic principles, techniques and tools of lean construction can already be applied. Waste reduction in order to improve performance is one of the basic concepts of lean thinking. In general, project managers tend to conceptualize "waste" as physical construction waste, but there are noticeable wastes in the construction processes which are named "non value-adding activities" by lean construction theory. In this paper, the waste quantity of construction processes in any format has determined through discrete event simulation based on lean thinking approach. Furthermore, a case study conducted to reveal the result of lean thinking application in a real manner. Results show that the construction processes have the high potential of optimization via implementing lean construction principles and computer simulation. © 2012 ASCE.